2018
DOI: 10.1021/acssuschemeng.7b04601
|View full text |Cite
|
Sign up to set email alerts
|

General Method to Correct the Fluctuation of Acid Based Pretreatment Efficiency of Lignocellulose for Highly Efficient Bioconversion

Abstract: Acid based pretreatment efficiency frequently changes with the varying properties of raw lignocellulose feedstock and creates disturbances in industrial biorefining applications. This study revealed that high alkaline ash content in feedstocks neutralized partial acid catalyst and consequently reduced the pretreatment efficiency. The ash content varies in each batch of feedstocks by differences in growing regions, seasons, irrigation, soil, fertilizer use, harvest operation, transportation, storage, and prehan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Bioconversion of lignocellulosic biomass into fuels and chemicals has attracted great interest over last few decades due to the increasing global energy demand, rural development, and environmental safety concerns [ 1 ]. Lignocellulosic biomass is mainly composed of cellulose, hemicellulose and lignin, while it also contains some minor components like ash and extractive in different samples [ 2 , 3 ]. Due to the recalcitrant structure of lignocellulose, commercial development of biomass and bioenergy is limited by the performance of cellulolytic enzyme systems [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioconversion of lignocellulosic biomass into fuels and chemicals has attracted great interest over last few decades due to the increasing global energy demand, rural development, and environmental safety concerns [ 1 ]. Lignocellulosic biomass is mainly composed of cellulose, hemicellulose and lignin, while it also contains some minor components like ash and extractive in different samples [ 2 , 3 ]. Due to the recalcitrant structure of lignocellulose, commercial development of biomass and bioenergy is limited by the performance of cellulolytic enzyme systems [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The acid catalyst usage for pretreatment was adjusted according to the method previously described (Han & Bao, 2018). A suspension slurry was prepared by mixing 2 g of raw feedstock (dry base) with 100 ml deionized water in a 250 ml flask, and then shaken vigorously at 30°C for 30 min, and the pH value of the slurry was measured by pH sensor.…”
Section: Methodsmentioning
confidence: 99%
“…The element contents were measured by inductively coupled plasma atomic emission spectrometry (725 ICP‐OES, Agilent) using the simultaneous CCD detector at 1.2 kW, 15 L/min of plasma gas flow, 1.5 L/min of auxiliary gas flow, 0.75 L/min of nebulizer flow, 15 rpm of pump speed, 35 s of sample delay time, and 10 s of stabilization time (Han & Bao, 2018). The samples were prepared by mixing 0.1 g of the ions containing solids or hydrolysate with 3 ml of nitric acid and 1 ml of perchloric acid, then boiled on an electric furnace for 4 h. All the liquid was then transferred into a flask and diluted with deionized water to 25 ml before used for detection.…”
Section: Methodsmentioning
confidence: 99%
“…Residual xylan in pretreated residues has been described to exert a "blocking effect" upon the substrate's surface, which renders unsuccessful enzymatic digestion [39]. To negate or eliminate the unwanted buffering effects caused by ash during autohydrolysis, strategies of de-washing and addition of sulfuric acid and exchangeable metal salts have been successfully applied in previous work [21,40,41]. Previous studies have also observed that the removal of organic matter alone from the soluble mixtures of EA can lead to an increasing enzymatic digestibility of autohydrolyzed WS with EA components [28].…”
Section: Effects Of Loading Buffering Compounds On the Enzymatic Digementioning
confidence: 99%